A Thermal Chemical Reaction System for Natural Gas Hydrates Exploitation - Wang, Yanan; Sun, Zhenxin; Li, Qingping; Lv, Xin; Ge, Yang (Frontiers in Energy Research, 2022)
The methodology of using CO2 to replace CH4 to recover the natural gas hydrates (NGHs) is supposed to avoid geological disasters. However, the reaction path of the CH4–CO2 replacement method is too complex to give satisfactory replacement efficiency. Therefore, this study proposed a thermochemical reaction system that used the heat and the nitrogen released by the thermochemical reactions to recover NGHs. The performance of the thermochemical reaction system (NaNO2 and NH4Cl) regarding heat generation and gas production under low temperature (4°C) conditions was evaluated, and the feasibility of exploiting NGHs with an optimized formula of the thermochemical reaction system was also evaluated in this study. First, the effects of three catalysts (HCl, H₃PO₄, and NH2SO3H) were investigated at the same reactant concentration and catalyst concentration. It was confirmed that HCl as a catalyst can obtain better heat generation and gas production. Second, the effect of HCl concentration on the reaction was investigated under the same reactant concentration. The results showed that the higher the HCl concentration, the faster is the reaction rate. When the concentration of HCl was greater than 14 wt%, side reactions would occur to produce toxic gas; hence, 14 wt% was the optimal catalyst concentration for the reaction of NaNO2 and NH4Cl at low temperatures. Third, the heat generation and gas production of the thermochemical reaction systems were evaluated at different reactant concentrations (1, 2, 3, 4, 5, and 6 mol/L) at 14 wt% HCl concentration. It was found that the best reactant concentration was 5 mol/L. Finally, the feasibility of exploiting NGHs with the optimal system was analyzed from the perspectives of thermal decomposition and nitrogen replacement. The thermochemical reaction system provided by this study is possible to be applied to explore NGHs’ offshore.